INHIBITORY MOTOR SEIZURES: SEMIOLOGY AND THERAPY - K. Yu. Мukhin; M. B. Мironov (Русский журнал детской неврологии)
The article is devoted to rare and unique type of epileptic seizures – inhibitory motor seizures, characterized by the inability to execute a voluntary movement with preserved consciousness. The exact prevalence of this type of seizures is not known, but many cases are unrecognized or non-correctly diagnosed as Todd's paralysis. Therefore practical doctors should know the clinical and electroencephalographic characteristics of this type of seizures andtake them into account in the differential diagnoses . The authors presented a detailed review of the literature, including the historical data, etiology, pathogenesis and proposed mechanisms of formation of inhibitory motor seizures, clinical and EEG characteristics, therapeutic approaches. Antiepileptic drugs of choice used in the treatment of inhibitory motor seizures are valproic acid (preferably depakine chronosphere – original prolonged form of valproate). The authors also presented their observations of patients with inhibitory motor seizures.